The Selection and Evaluation of Supplier: A Review and Perspective - Sirirak, Worapot; Jantakard, Harutairat; Luesak, Peerawat; Jinta-amornchai, Kumphol; Pinchaimoon, Amornrat; Sanguanpang, Somkuan; Seeta, Chatchai (RMUTL Engineering Journal, 2021)
This article was a literature review of supplier selection and evaluation. Several research articles were recently published and different methods and procedures of selecting and evaluating the supplier of organization were introduced. Therefore, this article aims to review criteria and methods in the supplier evaluation to identify important criteria that have great impact on businesses. In addition, this article is interested in using and evaluating analytical methods for decision making to select suppliers (i.e., AHP, ANP, DEA, Fuzzy Based Approach, and Hybrid), which can guide researchers and operators in selecting suitable methods and criteria. This can mitigate problems that occur as a result of improper supplier selection, e.g., the quality not meeting specifications, unrealistically high cost, as well as late delivery of product. This can also help increase the competitiveness of businesses.